Pharmacokinetic/pharmacodynamic (PK/PD) simulation for dosage optimization of colistin and sitafloxacin, alone and in combination, against carbapenem-, multidrug-, and colistin-resistant Acinetobacter baumannii - Rodjun, Vipavee; Montakantikul, Preecha; Houngsaitong, Jantana; Jitaree, Kamonchanok; Nosoongnoen, Wichit (Frontiers in Microbiology, 2023)
To the best of our knowledge, to date, no study has investigated the optimal dosage regimens of either colistin or sitafloxacin against drug-resistant Acinetobacter baumannii (A. baumannii) infections by using specific parameters. In the current study, we aimed to explore the optimal dosage regimens of colistin and sitafloxacin, either in monotherapy or in combination therapy, for the treatment of carbapenem-, multidrug-, and colistin-resistant A. baumannii infections. A Monte Carlo simulation was applied to determine the dosage regimen that could achieve the optimal probability of target attainment (PTA) and cumulative fraction of response (CFR) (≥90%) based on the specific parameters of each agent and the minimal inhibitory concentration (MIC) of the clinical isolates. This study explored the dosage regimen of 90, 50, 30, and 10 mL/min for patients with creatinine clearance (CrCL). We also explored the dosage regimen for each patient with CrCL using combination therapy because there is a higher possibility of reaching the desired PTA or CFR. Focusing on the MIC90 of each agent in combination therapy, the dosage regimen for colistin was a loading dose of 300 mg followed by a maintenance dose ranging from 50 mg every 48 h to 225 mg every 12 h and the dosage regimen for sitafloxacin was 325 mg every 48 h to 750 mg every 12 h. We concluded that a lower-than-usual dose of colistin based on specific pharmacokinetic data in combination with a higher-than-usual dose of sitafloxacin could be an option for the treatment of carbapenem-, multidrug-, and colistin-resistant. A. baumannii. The lower dose of colistin might show a low probability of adverse reaction, while the high dose of sitafloxacin should be considered. In the current study, we attempted to find if there is a strong possibility of drug selection against crucial drug-resistant pathogen infections in a situation where there is a lack of new antibiotics. However, further study is needed to confirm the results of this simulation study.